The relationship between immunization and food allergy and sensitisation in South African children - Ndhlovu, Nomathamsanqa (Department of Public Health and Family Medicine, 2017)
Abstract The prevalence of food allergies is higher in children compared to adults and it is increasing. The factors that influence food allergies in children are not clear. In light of the hygiene hypothesis, vaccinations may contribute towards to a predominant allergen specific response or exposure to the virus or microbe in the vaccine may decrease the risk for allergy. Previous studies have shown that the effect of vaccinations on food allergy and food sensitisation varies. Therefore, the aim of this study is to determine if a relationship exists between vaccinations and food allergies and food sensitisation in children in the first 18 months of life who live in urban Cape Town and in rural Mqanduli in the Eastern Cape. Secondary data analysis of an observational cross sectional study was carried out which involved univariate logistic regression to calculate odds ratios between self-reported immunisation status and food sensitisation and food allergy at a 95% confidence interval in children between 12 and 36 months of age. The same method was employed to investigate the relationship between immunisation and atopy. Multivariate analysis was utilised to adjust for potential confounders. Food sensitisation and food allergy were determined through skin prick tests (SPT) and oral food challenges respectively. The results indicate that, the number of participants positive for food sensitisation and allergy, eczema, hay fever and asthma were significantly greater in the urban sample (n= 708) compared to the rural sample (n= 400) (P<0.05). Further, in 708 urban children, those who had a BCG vaccine at birth were 0.05 (OR 0.05; 95% CI: 0.004 - 0.6) times less likely to have an SPT ≥ 7mm. The BCG unvaccinated cohort consisted of three individuals. There were no other significant associations between childhood vaccinations and food sensitization at SPT ≥ 1mm ,≥ 3mm and ≥ 7mm. There was no significant association between vaccinations and food allergy or other forms of atopy. In conclusion, there was very little evidence of an association between BCG vaccination in children and food allergic sensitisation or food allergy. However, in a small subgroup, there was evidence in an association between BCG and SPT ≥ 7 mm.